A relação entre conteúdo e forma nas políticas de educação profissional referenciadas no projeto de ensino médio integrado - PORTO, Adriana Maria Nazaré de Souza (2011)
As object of this study, we defined the concept of Integrated Learning and how to offer integrated secondary school to professional education expressed from the decree 5.154/2004 and have been a reference to recent educational public politics in the area of Professional Education. Our goal was to understand the contradiction that is imposed between content and form in education from the perspective of integration, which the treatment given by the politics and programs based on this concept in relation to the unitary character should advocate the relationship between form and content so the setting educational act. This is a bibliographical and documentary study, in which the content analysis was used for the treatment of research data in light of our analytical categories: praxis and totality. As main highlight : Frigotto (2003, 2005 and 2006), Kuenzer (1991, 2007 and 2009), Ramos (2005 and 2006), Frigotto, Ciavatta and Ramos (2005), Nosella (2004 and 2009), Marx (1844 and 1875), Manacorda (1991 and 2008), Vázquez (1976), Kosik (1926) and Pinto (2010). The result was the decoupled treatment of form and content politics and programs based on integration, the inability to build a public education politic that addresses these two dimensions as a unit contributing to the effective rupture of education duality.